2018
DOI: 10.1111/1471-0528.15467
|View full text |Cite
|
Sign up to set email alerts
|

Improving the effectiveness of lifestyle interventions for gestational diabetes prevention: a meta‐analysis and meta‐regression

Abstract: Four key effectiveness moderators of lifestyle interventions for GDM prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
2
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 68 publications
8
101
2
6
Order By: Relevance
“…Also, the results were in the same line with Guo et al, [21], in their Chinese study for increasing the effect of lifestyle programs about the prevention of gestational diabetes; as they revealed that practices in the form of nutrition and exercise within pregnancy were preventive of GDM (RR 0.77, 95% CI [0.69; 0.87]).…”
Section: Discussionsupporting
confidence: 85%
“…Also, the results were in the same line with Guo et al, [21], in their Chinese study for increasing the effect of lifestyle programs about the prevention of gestational diabetes; as they revealed that practices in the form of nutrition and exercise within pregnancy were preventive of GDM (RR 0.77, 95% CI [0.69; 0.87]).…”
Section: Discussionsupporting
confidence: 85%
“…Instead, interventions were most effective in populations with high incidence of GDM rather than simply in women who are overweight or obese. Furthermore, moderate intensity exercise for 50-60 min twice a week could lead to an approximately 24% reduction in GDM [12].…”
Section: Lifestyle Interventions To Prevent Gdmmentioning
confidence: 99%
“…Notwithstanding, recent reports showed that despite the extensive intervention of the Diabetes Prevention Program and Diabetes Prevention Study, almost 15% of women still had GDM 12 . Improving the lifestyle before pregnancy and postpartum gives insignificantly better results compare to dietary intervention 13 . The main issue of lifestyle improvement and diet management focuses on the firsttrimester time-points when methods for diagnosis of GDM and DF are still insensitive.…”
mentioning
confidence: 99%